Antiferromagnetism and superconductivity in the half-Heusler semimetal HoPdBi - Pavlosiuk, Orest (Nature Publishing Group, 2016)
We observed the coexistence of superconductivity and antiferromagnetic order in the single-crystalline ternary pnictide HoPdBi, a plausible topological semimetal. The compound orders antiferromagnetically at TN = 1.9 K and exhibits superconductivity below Tc = 0.7 K, which was confirmed by magnetic, electrical transport and specific heat measurements. The specific heat shows anomalies corresponding to antiferromagnetic ordering transition and crystalline field effect, but not to superconducting transition. Single-crystal neutron diffraction indicates that the antiferromagnetic structure is characterized by the propagation vector. Temperature variation of the electrical resistivity reveals two parallel conducting channels of semiconducting and metallic character. In weak magnetic fields, the magnetoresistance exhibits weak antilocalization effect, while in strong fields and temperatures below 50 K it is large and negative. At temperatures below 7 K Shubnikov-de Haas oscillations with two frequencies appear in the resistivity. These oscillations have non-trivial Berry phase, which is a distinguished feature of Dirac fermions.